Characterization and Classification of Soils and Land Suitability Evaluation for the Production of Major Crops at Anzecha Watershed, Gurage Zone, Ethiopia - Semu Moshago; Alemayehu Regassa; Teshome Yitbarek (Applied and Environmental Soil Science)
The study was conducted at Anzecha watershed in Gurage Zone, Ethiopia, to characterize and classify the soils and to evaluate the physical land suitability of the area for the production of major crops (maize, teff, and wheat). The soils were classified based on World Reference Base for soil resource. The physical land suitability was made following FAO guideline using maximum limitation method. Four profiles were opened along toposequence and designate as upper, middle, lower, and toe slope positions (pedons 1, 2, 3, and 4), respectively. Soils of the watershed had low level of available phosphorous, low electrical conductivity, no coarse fragments, low acidity, and great depth. The soils were classified as Acrisols, Nitisols, and Vertisols. The land suitability evaluation for production of major crops showed that upper slope position (20.8%) was currently not suitable (N1) for maize, teff, and wheat. Middle slope position (27.3%) was marginally suitable (S3) for maize, teff, and wheat. Lower slope position (32.5%) was moderately suitable (S2) for maize and marginally suitable (S3) for teff and wheat. Toe slope position (19.4%) was moderately suitable (S2) for maize and teff and marginally suitable (S3) for wheat. There is no topographic position that was classified as highly suitable (S1). Hence, farmers of the area should implement major land improvement practice to create optimum condition for production of major crops or should change a land utilization type. Moreover, the soils of the study area were acidic and, therefore, there has to be acid soils management strategy in the area.